Assessing chemical composition variations on vintage, vineyard location and grape ripeness: A regional study of red wines produced in the colorado river middle basin, La Pampa (Argentina) - Varela, Ayelén Celeste; Wagner, Marcelo; Masseroni, Maria Lujan; Sartor, Paolo Daniel; Zaldarriaga Heredia, Jorgelina; Jofré, Florencia Cora; Sari, Santiago Eduardo; Catania, Anibal Alejandro; Prieto, Jorge Alejandro; Savio, Marianela; Camiña, José Manuel; Azcarate, Silvana; et al. (Elsevier, 2024)
This work aimed to characterize chemical composition of Malbec and Cabernet Franc red wines from two different regions of La Pampa’s province, which stands out as one of the youngest wine-producing regions in Argentina and has remained unexplored until now. These wines were produced from grapes of two consecutive vintages (2021 and 2022), and were harvested at two different ripeness levels. Global phenolic parameters, colour characterization and multi-elemental profile were evaluated. Multivariate statistical approaches were successfully implemented to investigate the vintage and ripeness effects on chemical profile of red wines and characterize them based on regional variations. Our results showed that vintage and ripeness affected both phenolic and multi-elemental profiles, and such chemical variables allowed the wines differentiation according to region. The results of this first study could form the basis for future research into optimizing the region’s winemaking potential.